Retinal nerve fiber layer thickness analysis in normal, ocular hypertensive, and primary open angle glaucoma: an optical coherence tomography study - Patel, Dipak; Rana, Poonam; Dua, Siddharth; Patel, Roshni (International Journal of Research in Medical Sciences, 2018)
Background: To correlate the findings of optical coherence tomography (OCT) evaluation of retinal nerve fiber layer (RNFL) thickness in primary open angle glaucoma, ocular hypertensive and normal eyes. Methods: A 34 consecutive normal, 26 consecutive ocular hypertensives and 40 consecutive glaucomatous eyes underwent a complete ophthalmic examination, including applanation tonometry, disc evaluation, gonioscopy and perimetry. Thickness of the RNFL around the optic disc was determined with 3.4 mm diameter-wide 3D 2000 TOPCON OCT. Average and segmental RNFL thickness values were compared among all groups. Results: Of the 100 eyes enrolled, the mean RNFL thickness was significantly less in glaucomatous eyes (83.165±15.938) than in normal’s (102.42±15.2) and ocular hypertensive’s (100.45±7.38). RNFL, average thicknesses in all four quadrants in POAG patients were significantly decreased compared with the OHT and the control groups. Conclusions: RNFL measurement with SD-OCT could provide important information for detection of early stages of glaucoma. (pre-perimetric glaucoma) as well as help in evaluating progression of glaucoma.